Loss of Ranbp2 in motoneurons causes disruption of nucleocytoplasmic and chemokine signaling, proteostasis of hnRNPH3 and Mmp28, and development of amyotrophic lateral sclerosis-like syndromes - Kyoung-in Cho; Dosuk Yoon; Sunny Qiu; Zachary Danziger; Warren M. Grill; William C. Wetsel; Paulo A. Ferreira (The Company of Biologists, 2017)
The pathogenic drivers of sporadic and familial motor neuron disease (MND), such amyotrophic lateral sclerosis (ALS), are unknown. MND impairs the Ran GTPase cycle, which controls nucleocytoplasmic transport, ribostasis and proteostasis; however, cause-effect mechanisms of Ran GTPase modulators in motoneuron pathobiology have remained elusive. The cytosolic and peripheral nucleoporin Ranbp2 is a crucial regulator of the Ran GTPase cycle and of the proteostasis of neurological disease-prone substrates, but the roles of Ranbp2 in motoneuron biology and disease remain unknown. This study shows that conditional ablation of Ranbp2 in mouse Thy1 motoneurons causes ALS syndromes with hypoactivity followed by hindlimb paralysis, respiratory distress and, ultimately, death. These phenotypes are accompanied by: a decline in the nerve conduction velocity, free fatty acids and phophatidylcholine of the sciatic nerve; a reduction in the g-ratios of sciatic and phrenic nerves; and hypertrophy of motoneurons. Furthermore, Ranbp2 loss disrupts the nucleocytoplasmic partitioning of the import and export nuclear receptors importin β and exportin 1, respectively, Ran GTPase and histone deacetylase 4. Whole-transcriptome, proteomic and cellular analyses uncovered that the chemokine receptor Cxcr4, its antagonizing ligands Cxcl12 and Cxcl14, and effector, latent and activated Stat3 all undergo early autocrine and proteostatic deregulation, and intracellular sequestration and aggregation as a result of Ranbp2 loss in motoneurons. These effects were accompanied by paracrine and autocrine neuroglial deregulation of hnRNPH3 proteostasis in sciatic nerve and motoneurons, respectively, and post-transcriptional downregulation of metalloproteinase 28 in the sciatic nerve. Mechanistically, our results demonstrate that Ranbp2 controls nucleocytoplasmic, chemokine and metalloproteinase 28 signaling, and proteostasis of substrates that are crucial to motoneuronal homeostasis and whose impairments by loss of Ranbp2 drive ALS-like syndromes.